Relationships among musical aptitude, digit ratio and testosterone in men and women. - Jeremy C Borniger (Public Library of Science (PLoS), 2013)
Circulating adult testosterone levels, digit ratio (length of the second finger relative to the fourth finger), and directional asymmetry in digit ratio are considered sexually dimorphic traits in humans. These have been related to spatial abilities in men and women, and because similar brain structures appear to be involved in both spatial and musical abilities, neuroendocrine function may be related to musical as well as spatial cognition. To evaluate relationships among testosterone and musical ability in men and women, saliva samples were collected, testosterone concentrations assessed, and digit ratios calculated using standardized protocols in a sample of university students (N = 61), including both music and non-music majors. Results of Spearman correlations suggest that digit ratio and testosterone levels are statistically related to musical aptitude and performance only within the female sample: A) those females with greater self-reported history of exposure to music (p = 0.016) and instrument proficiency (p = 0.040) scored higher on the Advanced Measures of Music Audiation test, B) those females with higher left hand digit ratio (and perhaps lower fetal testosterone levels) were more highly ranked (p = 0.007) in the orchestra, C) female music students exhibited a trend (p = 0.082) towards higher testosterone levels compared to female non-music students, and D) female music students with higher rank in the orchestra/band had higher testosterone levels (p = 0.003) than lower ranked students. None of these relationships were significant in the male sample, although a lack of statistical power may be one cause. The effects of testosterone are likely a small part of a poorly understood system of biological and environmental stimuli that contribute to musical aptitude. Hormones may play some role in modulating the phenotype of musical ability, and this may be the case for females more so than males.